2015
DOI: 10.1038/cdd.2015.95
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a impairs autophagy and induces cardiac hypertrophy through mTOR activation

Abstract: Basal autophagy is tightly regulated by transcriptional and epigenetic factors to maintain cellular homeostasis. Dysregulation of cardiac autophagy is associated with heart diseases, including cardiac hypertrophy, but the mechanism governing cardiac autophagy is rarely identified. To analyze the in vivo function of miR-199a in cardiac autophagy and cardiac hypertrophy, we generated cardiac-specific miR-199a transgenic mice and showed that overexpression of miR-199a was sufficient to inhibit cardiomyocyte autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 37 publications
5
115
0
2
Order By: Relevance
“…Consistently, the hypertrophic effects of miR-199a could be reversed by overexpression of Atg5 or rapamycin treatment [119]. Similar results have been obtained in studies focusing on miR-30-Ang II [120], miR-34a-Ang II [121], and miR-451-tuberous sclerosis complex 1 [122] autophagy-mediated cardiomyocyte hypertrophy.…”
Section: Therapeutic Potential Of Autophagic Modulation In Chronic Hesupporting
confidence: 84%
“…Consistently, the hypertrophic effects of miR-199a could be reversed by overexpression of Atg5 or rapamycin treatment [119]. Similar results have been obtained in studies focusing on miR-30-Ang II [120], miR-34a-Ang II [121], and miR-451-tuberous sclerosis complex 1 [122] autophagy-mediated cardiomyocyte hypertrophy.…”
Section: Therapeutic Potential Of Autophagic Modulation In Chronic Hesupporting
confidence: 84%
“…In addition, the expression level of miR-199a-5p was significantly increased in gastric cancer tissues compared with paired normal tissues, and higher miR-199a-5p level was associated with increased lymph node metastasis and higher tumor-node-metastasis stage, suggesting that miR-199a-5p may act as an oncogene in gastric cancer (26). Recently, miR-199a-5p has been reported to exhibit inhibitory effects on autophagy (27). For instance, Lee et al observed that protoporphyrin IX, a photocatalyzer, could increase the expression of miR-199a-5p, which further inhibited E2F transcription factor 3 and sensitized mesenchymal tumor cells to chemotherapy drugs (28).…”
Section: Mir-199a-5p Negatively Mediates the Protein Expression Of Bementioning
confidence: 97%
“…Several miRNAs that induce pathological hypertrophy and heart failure have been identified, such as miR-195, miR-21, miR23a and miR-208a, whereas miR-133 and miR-1 negatively regulate cardiac hypertrophy (Yang et al 2011). Many studies have shown that miRNAs regulate both cardiac hypertrophy and cardiomyocyte autophagy, for example, miR-212/132 and miR-199a; induce cardiac hypertrophy; and attenuate the autophagic response in cardiomyocytes (Ucar et al 2012, Li et al 2015a. Ang II-induced cardiomyocyte hypertrophy in terms of cell area of cardiomyocytes and expression of the cardiomyocyte hypertrophy markers atrial natriuretic peptide (ANP) and β-myosin heavy chain (β-MHC) mRNA; moreover, the level of ATG9A protein and mRNA expression was upregulated.…”
Section: Effects Of Microrna In Ang Ii-induced Autophagymentioning
confidence: 99%